Introduction: American Game Studies - Jagoda, Patrick; Malkowski, Jennifer (American Literature, 2022)
In 2017, the American game designer Momo Pixel released the single-player, browser-based game Hair Nah. In this game, you play as Aeva, a Black woman taking trips to locations that include Osaka, Havana, and the Santa Monica Pier. As you move through levels on your journey—taking a taxi ride, traversing airport security, sitting on an airplane—you must slap away increasingly aggressive white hands that reach into the frame to touch your hair. Though Hair Nah taps into the genre of a casual button-mashing game, this interactive experience also explores the topic of microaggressions via unwanted hair touching. If you slap away enough hands on your travels, you reach a screen welcoming you to your destination with the message “YOU WIN!” but the caveat, “The game is over, but this experience isn’t. This is an issue that black women face daily. So a note to those who do it STOP THAT SHIT.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

“My Whole Life I’ve Been on the Run”: Fugitivity as a Postracial Trope in Red Dead Redemption 2 - Marks, Katrina (American Literature, 2022)
This article discusses the popular video game Red Dead Redemption 2 (2018) by Rockstar Games, which follows Arthur Morgan, a white outlaw, during the decline of the “Wild West” in 1898 and 1899. Taking up conversations of fugitivity in critical ethnic studies, this article maintains that fugitivity operates as a rhetorical trope that stands in for racial identity where the logic of postracialism denies investments in race. Analyzing the narrative, spatial, and kinesthetic elements of the game, this article argues that Morgan, and by extension the player, is aligned with historically and geographically racialized others through a fugitive relationship to space. While Rockstar, as a video game studio, may not see itself explicitly intervening in a racialized and racializing political imaginary in its fictional worldbuilding, the kinesthetic, narrative, and cartographic strategies the studio employs respond to a set of cultural assumptions rooted in the rhetoric of postracialism. As such, Red Dead Redemption 2 serves as a multifaceted text through which to interrogate the dynamics of that rhetoric as it is mobilized in representations of fugitivity and identity.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Reconsidering Lost Opportunities for Diverse Representation - Nguyen, Josef (American Literature, 2022)
This article considers the cultural politics of frustrated potential for diverse representation in games by examining developer comments on the 1995 digital game I Have No Mouth, and I Must Scream, adapted from Harlan Ellison’s 1967 science fiction story of the same name. While Ellison’s story featured a gay man named Benny among the protagonists, the game developers adapted Benny without his original sexual identity. In a 2012 Game Informer magazine article, however, the developers reflected on their version of Benny as a “lost opportunity” for exploring gay identity. Rooted in discussion of this frustrated potential for a gay in-game Benny, this article interrogates a logic of lost opportunity for diverse representation present in game-development discourse, which manifests in a longing for more diverse characters that could have been but never came to be. This logic suggests particular ways that developers might conceive of diverse representation as simply a design issue under neoliberal logics of economic opportunity, commercial risk, and fetishized innovation—without meaningful consideration of political significance. Opposing this instrumentalization of frustrated diverse representation, this article draws on queer game studies and speculative design and literature to explore the possible contours and implications of diverse characters that never were more seriously than such comments typically do. Doing so demands more than romanticized longings for lost opportunities for diverse representation that treat this longing as the end in itself.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Making Queer Asiatic Worlds: Performance and Racial Interaction in North American Visual Novels - Patterson, Christopher B. (American Literature, 2022)
This paper argues that video games expose the presumptions separating “Asian America” and “Asia” in the traditional senses of isolation, origination, and presumed distance. It does so by focusing on the most “Asiatic” genre of video games today, the North American visual novel, which offers a counterdiscourse to normative modes of play and attempts to offer utopic spaces to reflect upon the “real” genres of race and neo–Cold War geopolitics. Using theories of performance from Dorinne Kondo and others, the author shows how queer indie visual novels are primarily aspirational, in that they build queer, utopic, and seemingly anti-racist worlds through the Asiatic space of the visual novel form. In so doing, they also allow players to explore the Asiatic as a means of repairing the traumas and distances of American imperial cultures. The article analyzes four visual novels to make this argument: three by non-racially-identifying North American designers—Doki Doki Literature Club! (2017) by Dan Salvato, Analogue: A Hate Story (2012) by Christine Love, and Heaven Will Be Mine (2018) by Aevee Bee—and Butterfly Soup (2017), a game by the queer Asian/American designer Brianna Lei. If games make the boundaries of Asia and America irrelevant, visual novels explore this irrelevance through Asiatic irreverence.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

The Mystery of the Missing AIDS Crisis: A Comparative Reading of Caper in the Castro and Murder on Main Street - Ruberg, Bo (American Literature, 2022)
This article addresses the seeming absence of the HIV/AIDS pandemic in video games from the 1980s and 1990s, the height of the US AIDS crisis. As Adrienne Shaw and Christopher Persaud have noted, stories about HIV/AIDS were pervasive across American popular media during this period, which also represented a boom in video game development. However, documentation remains of only a handful of early video games that mention HIV/AIDS. This article argues that, far from being absent from video game history, HIV/AIDS and the US AIDS crisis were actually influential in shaping a number of the design elements and narrative genres that have become important to contemporary video games. Scholars like Cait McKinney have demonstrated how people living with HIV/AIDS in America played a crucial part in the evolution of internet technologies that now form the backbone of video games. Through a comparative reading of two games by C. M. Ralph, Caper in the Castro (1989) and Murder on Main Street (1989), this article demonstrates how HIV/AIDS has also manifested in the content and form of video games, even (and perhaps especially) when it seems absent. Derritt Mason has explained how Caper in the Castro, widely celebrated as the first LGBTQ video game, contains clear echoes of the AIDS crisis. Yet, as this article demonstrates, HIV/AIDS remains a powerful presence even in Murder on Main Street, Ralph’s “straight version” of the game. Together, these games offer a microcosm through which to explore larger tensions between HIV/AIDS and video games, with the AIDS crisis representing a key element of what Cody Mejeur has termed the “present absence of queerness in video games.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Professional Norms and Race in the North American Video Game Industry - Srauy, Sam (Games and Culture, 2019)
This article examines North American (i.e., Canada and the United States) video game developers’ understanding of race, how they construct narratives when they include characters of different races, and some of the pressures that may shape that process. Discourse analyses of semistructured interview texts found that video game developers operate under an internalized pressure to create game narratives that are quickly understandable and, thus, sellable. This pressure is normatively internalized in the profession as an attempt to hedge against market uncertainty. Video game developers, therefore, depend on social beliefs from the “real world” to inform how video game players might receive their games as well as narratives and themes from past texts such as the works of J. R. R. Tolkien. Therefore, this article argues that racism might be enabled because it is believed to be a hedge against market uncertainty.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Realism in FIFA? How Social Realism Enabled Platformed Racism in a Video Game - Srauy, Sam; Cheney-Lippold, John (First Monday, 2019)
Platformed racism offers a unique lens through which to investigate technological structures that enable racism. Online video games, such as EA Sports’ FIFA series — which dominates the soccer video game market share through its touted realism — feature these structures. Like many platforms, FIFA enables representations of real bodies (i.e., professional soccer players). But, unlike many games, FIFA enables game players to directly affect the creation/modification of these representation in the form of player character cards. Analyzing a census of six years of player cards, this study found that platformed racism was enabled because the game’s realism invited racism when players tried to maintain that realism. The study concludes that the catalyst for racism to emerge in FIFA was the drive towards realism.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Slave Revolt on Screen: the Haitian Revolution in Film and Video Games - Sepinwall, Alyssa Goldstein (Caribbean studies series, 2021)
In Slave Revolt on Screen: The Haitian Revolution in Film and Video Games author Alyssa Goldstein Sepinwall analyzes how films and video games from around the world have depicted slave revolt, focusing on the Haitian Revolution (1791–1804). This event, the first successful revolution by enslaved people in modern history, sent shock waves throughout the Atlantic World. Regardless of its historical significance however, this revolution has become less well-known—and appears less often on screen—than most other revolutions; its story, involving enslaved Africans liberating themselves through violence, does not match the suffering-slaves-waiting-for-a-white-hero genre that pervades Hollywood treatments of Black history. Despite Hollywood’s near-silence on this event, some films on the Revolution do exist—from directors in Haiti, the US, France, and elsewhere. Slave Revolt on Screen offers the first-ever comprehensive analysis of Haitian Revolution cinema, including completed films and planned projects that were never made. In addition to studying cinema, this book also breaks ground in examining video games, a pop-culture form long neglected by historians. Sepinwall scrutinizes video game depictions of Haitian slave revolt that appear in games like the Assassin’s Creed series that have reached millions more players than comparable films. In analyzing films and games on the revolution, Slave Revolt on Screen calls attention to the ways that economic legacies of slavery and colonialism warp pop-culture portrayals of the past and leave audiences with distorted understandings.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

Young, Black (& Brown) and Don't Give a Fuck: Virtual Gangstas in the Era of State Violence - Leonard, David (Cultural Studies ↔ Critical Methodologies, 2009)
The popularity and visibility of video games within American popular culture is prompted debates within from a spectrum of institutions, ranging from the media and the academy to Main Street and the political sphere. Erasing the complexity, much of the discourse focuses instead on questions of violence and the impact of gaming culture on (White) American youth. While focusing on Grand Theft: San Andreas specifically, this essay explores the culture wars surrounding American video game culture, arguing that the moral panics directed at video games and the defenses/celebrations of virtual reality operate through dominant discourses and hegemonic ideologies of race. Erasing their racial content and textual support for state violence directed at communities of color, the dominant discourse concerning youth and video games rationalizes the fear and policing of Black and Brown communities.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Problématiques de l'imaginaire du Nord en littérature, cinéma et arts visuels - Bouchard, Joë; Chartier, Daniel; Nadeau, Amélie (Collection "Figura", 2004)
Conçu comme un discours et non comme un simple référent géographique, le Nord se déploie dans des formes littéraires et culturelles qui en déterminent les particularités. Pluriculturel, variable selon les époques, les lieux et les points de vue, le Nord ouvre des problématiques sur les liens entre le référent et la représentation, entre le discours et l'imaginaire. Qu'il soit scandinave, québécois, finlandais, inuit ou européen, qu'il se manifeste dans les récits, les films, les romans, la poésie, la photographie ou les arts visuels, qu'il soit le lieu d'une dénonciation post-coloniale ou d'un discours impérialiste, d'une recherche formelle ou de l'expression de la culture populaire, le discours du Nord et sur le Nord converge en des paradigmes et des problématiques qui lui sont propres. Dans ce recueil, issu des travaux du Laboratoire international d'étude multidisciplinaire comparée des représentations du Nord et initié par la tenue d'un colloque organisé en décembre 2003 par Joël Bouchard et Amélie Nadeau, le lecteur trouvera quelques pistes d'analyse pour saisir la complexité du système discursif du Nord, réparties en trois sections intitulées: «Formes et intertextualité», «Territoires», ainsi que «Iconographie, voyages, et cinéma».
Keywords: 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Transformations and Remembrances in the Digital Game We Sing for Healing - LaPensee, Elizabeth A. (Transmotion, 2017)
Digital games, with their capacity for expression and facilitating experience through code, design, art, and audio, offer spaces for Indigenous creatives to contribute to Gerald Vizenor’s characterization of survivance as an active sense of Native presence. Indigenous digital games can be acts of survivance both in the ways they are created as well as the resulting designs. We Sing for Healing is an experiment in developing an Indigenous digital game during limited Internet access that resulted in a musical choose-your-own adventure text game with design, art, and code by Anishinaabe, Métis, and Irish game developer Elizabeth LaPensée alongside music by Peguis First Nation mix artist Exquisite Ghost. The non-linear gameplay expresses traditional storytelling patterns while enabling players to poetically travel in, through, and around traditional teachings. The design uses listening, choosing, and revisiting to reinforce what is best described as a non-linear loopular journey.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Honour water: Gameplay as a Pathway to Anishinaabeg Water Teachings - LaPensée, Elizabeth (Decolonization: Indigeneity, Education & Society, 2018)
Digital games can uniquely express Indigenous teachings by merging design, code, art, and sound. Inspired by Anishinaabe grandmothers leading ceremonial walks known as Nibi Walks, Honour Water (http://www.honourwater.com/) is a singing game that aims to bring awareness to threats to the waters and offer pathways to healing through song. The game was developed with game company Pinnguaq and welcomes people from all over to sing with good intentions for the waters. The hope is to pass on songs through gameplay that encourages comfort with singing and learning Anishinaabemowin. Songs were gifted by Sharon M. Day and the Oshkii Giizhik Singers. Sharon M. Day, who is Bois Forte Band of Ojibwe and one of the founders of the Indigenous Peoples Task Force, has been a leading voice using singing to revitalize the waters. The Oshkii Giizhik Singers, a community of Anishinaabekwe who gather at Fond du Lac reservation, contribute to the healing for singers, communities, and the waters. Water teachings are infused in art and writing by Anishinaabe and Métis game designer, artist, and writer Elizabeth LaPensée. From development to distribution, Honour Water draws on Indigenous ways of knowing to reinforce Anishinaabeg teachings with hope for healing the water.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

SPEAR: a Framework for Indigenous Cultural Games - LaPensee, Elizabeth (ANTARES: Letras e Humanidades, 2020)
Video games, which uniquely interweave design, code, art, and sound, can be an especially robust way to express Indigenous cultures. Such games should involve Indigenous people in meaningful roles throughout design and development from conceptualization to distribution with a focus on building capacity to encourage self-determination for Indigenous game developers. This call to action informs SPEAR (Sovereignty, Positionality, Equity, Advocacy, and Reciprocity), a framework for design and development informed by the Indigenous cultural game Thunderbird Strike.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Recherche-création; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I see my ancestors”: Exploring Tribal College Student Experiences Playing When Rivers Were Trails - Emmons, Nichlas; LaPensee, Elizabeth (AlterNative: An International Journal of Indigenous Peoples, 2021)
The educational video game, When Rivers Were Trails, was launched in 2019. The purpose of the game is to teach players about Indigenous perspectives of history, US federal allotment policies affecting tribal nations, and some of the effects of these policies on Indigenous peoples. This article explores tribal college student experiences playing When Rivers Were Trails in hopes that it provides the basis for further research into how tribal college faculty may be able to teach the game within their own classrooms. Tribal colleges and universities were created by tribal nations to provide for the higher education needs of their citizens. Using phenomenological research methods, seven college students volunteered to participate in a brief study about their experiences playing the video game. Upon transcription and analysis of the interview data, three themes were developed that capture how these students define their experience with When Rivers Were Trails: feelings of representation, histories of land dispossession, and resilience of communities.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Towards Sovereign Games - LaPensée, Elizabeth A.; Laiti, Outi; Longboat, Maize (Games and Culture, 2021)
Video games can be dynamic sovereign spaces for Indigenous representation and expression when the self-determination of Indigenous people is supported. Where ga...
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge Companions, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Digital Dispossessions: the Importance of Regional Specificity and Sovereign Spaces to Video Game Representations of Native American Cultural Heritage - Bird, Ashlee (Studia Neophilologica, 2021)
Indigenous peoples and their cultural heritages, their ways of knowing and living, are tied to land. As Mishuana Goeman states,“Land is foundational to people’s cultural practices, and if we define culture as meaning making rather than as differentiation and isolation in a multicultural neoliberal model, thanby thinking through land as a meaning-making process rather than a claimed object, the aspiration of Native people are apparent and clear,” (Goeman, 73).Goeman asserts here that land is not limited to physical space, and that land locates a group of people physically, culturally, spiritually, intellectually,etc. and provides them with both an internal and external locus of understanding for and within broader society. When digital representations of Indigenous peoples are completely removed from any meaningful connection to their land, anerasure of culture occurs. Moreover, the physical removal of Indigenous peoples from the virtual representations of their lands is another form of dispossession and the enactment of digital Manifest Destiny. This paperutilizes a decolonial Indigenous framework to analyze the dispossessions that take place within the digital realm of the video game, why they occur so frequently, and why they are so harmful.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Examining the Intersection of Race and Gender in Video Game Advertising - Behm-Morawitz, Elizabeth (Journal of Marketing Communications, 2017)
Women and racial/ethnic minorities account for a growing percentage of video game players in the USA. The economic future of the video game industry may, in part, depend on the industry's ability to adapt marketing efforts to appeal to the growing female and racial/ethnic markets. Contrary to these efforts, however, is advertisers' reliance on stereotypes in advertisements to quickly establish a common understanding and wide appeal to a mass audience. This study investigates how race and gender intersect in the stereotypical character depictions used to market video games to consumers. A systematic content analysis was carried out of 383 US magazine advertisements of console, mobile, and PC video games. Stereotyping and intersectionality literatures were used as theoretical guides for this research. Findings reveal that the marketing of video games in the USA upholds some longstanding media stereotypes of minorities and women, including that of the White male hero, submissive sexualized female, Asian ninja, and deviant Black male. The potential social and economic implications of the video game industry's reliance on character stereotypes for the marketing of video games are discussed.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Indigenous Representations and the Impacts of Video Games Media on Indigenous Identity - Lagace, Naithan (University of Manitoba, 2018)
This thesis analyzes and discusses the complexities of digital representations involving Indigenous peoples through video games. Connecting both Game Theory and Native Studies, I analyze how digital games incorporate identity, culture, and relationships in diverse and intellectual ways and provide new spaces for Indigenous agency and semiotics. Beginning with an analysis of several historical and negative representations of Indigenous peoples, I then compare those tropes to projects within today’s environment and mainstream video game companies, independent companies, and educational service providers. I assert that while some digital media representations of Indigenous cultures are stereotypical and problematic, others facilitate a sense of cultural continuance and survivance. Lastly, some video games display both stereotypical and cultural continuance within them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“We All Stand Side by Side”: An Interview with Elizabeth LaPensée - Hearne, Joanna (Studies in American Indian Literatures, 2017)
Keywords: 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Histoire de l'art

Coming to You from the Indigenous Future: Native Women, Speculative Film Shorts, and the Art of the Possible - Medak-Saltzman, Danika (Studies in American Indian Literatures, 2017)
Keywords: 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Imagining Indigenous Digital Futures: An Afterword - Raheja, Michelle (Studies in American Indian Literatures, 2017)
In lieu of an abstract, here is a brief excerpt of the content: As I sit writing in my kitchen while the forces of the U.S. military state are brought to bear on thousands of Standing Rock water stewards and land protectors and their allies in Cannonball, North Dakota, I consider how this sail special issue on digital Indigenous studies not only represents a collection of essays about the critical work Indigenous women are performing in their various digital projects but also illustrates that these online “Indigenous territories” (Hearne), crafted on social media platforms such as Twitter and Facebook, save lives. Every single day since the protectors first gathered to oppose the proposed 1,170-mile Dakota Access pipeline (a project that would potentially contaminate the Missouri watershed and the Ogallala Aquifer and desecrate Dakota sacred sites), digital independent and social media have constantly covered the story. At least 1.3 million Facebook users checked in virtually at Oceti Sakowin and other Indigenous camps and communities to ensure that support presence is recognized, while the world monitors the presence of the military and police force gathering at the construction site to curb further violence. The Standing Rock gathering offers hope to networked Indigenous youth, a demographic between three and ten times as likely to commit suicide than the national average peer rate. The Nodapl action in the Indigenous imaginary is an invitation to stand at the front lines of a global movement to protect water and land resources for all living beings on this planet and to draw attention to and support those whose lives and ways of being are in peril through overt military action and consequential environmental destruction. It is also an occasion, in the words of Jolene Rickard, “to invest in the apparatus of the imagination” (Bernardin). One need only look at the online art, handwritten signs, and logos representing #nodapl, #standingrock, [End Page 172] #waterislife, and #rezpectourwater to see the ways in which Indigenous artists are creatively and powerfully envisioning this movement, most often immersed with work that features strong images of Native women and girls, the community backbone and life force. Or we need only view digital videos like computer animator and artist Joseph Erb’s black-and-red graphic history of Standing Rock, “Mni Wiconi / Water Is Life” (https://www.youtube.com/watch?v=kXoy5lzpjiM), and first-person game platforms like Elizabeth LaPensée’s Thunderbird Strike, which extend the conversations at Standing Rock to the struggles over Enbridge’s Alberta tar sands pipeline and fracking practices as players work to undo and prevent further environmental degradation. Following Idle No More’s digital and geospatial (re)articulation of Indigenous territories, we are now living and loving and hoping in this historic moment as new ways of relating to one another and living in deep connection with the land and all its forms of life are being physiologically, intellectually, and spiritually forged at the geospatial confluence of the Missouri and Cannonball Rivers. They are being forged as well through the confluences of digital rivers on our electronic devices and in our online conversations about the beauty and devastation of the events that are unfolding in Standing Rock. Susan Bernardin’s essay in this issue on Heid E. Erdrich’s “Pre-Occupied” considers the meaning of rivers to Native peoples and contends that images of waterways, particularly the Mississippi, are mobilized “to make visible the continuing claims of this and other imperiled riverine systems.” In her introduction, Joanna Hearne asks us, “How might such an intersection of digital and Indigenous specificities take place in a way that is ‘native to the device’; that is, how might Indigenous specificity be embedded in shared platforms that are therefore central to all of our digital lives?” The essays in this special issue respond to this question by theorizing digital media in fresh and innovative ways. Many of us teach digital humanities courses or classes with strong digital media content, but we lack the language for critically engaging this new field on its own terms as it intersects, extends, and radically reconceptualizes more familiar research areas such as cinema studies, Indigenous / Native American studies, communication, literature, art, and history.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Thunderbird Strike: Survivance in/of an Indie Indigenous Game - LaPensée, Elizabeth (Video Game Art Reader 2.1, 2018)
Thunderbird Strike, a 2D side-scroller developed by Elizabeth LaPensée, allows a player fly from the Tar Sands to the Great Lakes as a thunderbird protecting Turtle Island with searing lightning against the snake that threatens to swallow the lands and waters whole. The game encouraged players to learn about the indigenous culture, reflect on water protection and alternative energy sources, and gain awareness of risks posed by oil pipeline construction for the conveyance of tar sands.Thunderbird Strike was developed through residencies including O k’inādās Residency, The Banff Musicians in Residence Program, and Territ-Aur(i)al Imprints Exchange thanks to the 2016 Artist Fellowship grant from the Arrowhead Regional Arts Council.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Critical Protocols in Indigenous Gamespace - Miner, Joshua D. (Games and Culture, 2022)
This article examines Indigenous video games that critique mainstream environmental politics at the level of mechanics. An analysis of video games’ influences on ecological values requires looking beyond the representational to the mechanical relationships between player and software. As a cultural–computational medium, video games are embedded with ethics of interaction that inflect this representational dimension by requiring that players generate the text as participant. With the recent visibility of Indigenous rights movements, developers have embedded Indigenous cultural protocols in the mechanical interactions (or technical protocols) of gameplay. In the context of critique, their integration produces “critical protocols,” configurations of gamic action that encourage players to evaluate their treatment of real-world environments. Critical protocols emerge between the technical and cultural, where scripts for interaction in algorithmic spaces intervene in affirmative game design and work as an analog beyond the game. Indigenous developers call for new ways of computing and critiquing settler digitality through play. These games aim toward representational as well as computational sovereignty.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le jeu vidéo comme vecteur d’expression du patrimoine culturel des Iñupiats d’Alaska - Hocine, Julien; Deslauriers, Patrick (Emulations - Revue de sciences sociales, 2019)
En 2014, une collaboration entre le studio Upper One Games et des conteurs et aînés iñupiats d’Alaska a mené au lancement du jeu vidéo Kisima Inŋitchuŋa (Never Alone). Ce jeu de plateforme invite à une immersion poétique dans un univers nordique guidée par une trame narrative inspirée d’une légende traditionnelle. Dans une perspective culturelle, les fonctions ludique et documentaire du jeu permettent d’acquérir des connaissances en lien avec les pratiques traditionnelles et la vision du monde des Iñupiats. Ainsi, l’étude exploratoire présentée dans cet article contribue à comprendre les caractéristiques du jeu (design, narration, mécaniques) et les stratégies relevant de sa conception. Les résultats invitent à reconsidérer des représentations dominantes du Grand Nord et soulignent en quoi le jeu vidéo se fait vecteur d’expression du patrimoine culturel, artistique et oral d’un peuple autochtone de l’Arctique.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Exploring the Difficulties African-American Middle School Girls Face Enacting Computational Algorithmic Thinking over three Years while Designing Games for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Minor, Rachelle; Sun, Li (Computer Supported Cooperative Work, 2017)
Computational algorithmic thinking (CAT) is the ability to design, implement, and assess the implementation of algorithms to solve a range of problems. It involves identifying and understanding a problem, articulating an algorithm or set of algorithms in the form of a solution to the problem, implementing that solution in such a way that the solution solves the problem, and evaluating the solution based on some set of criteria. CAT is an important scaffolded on-ramp as students develop more advanced computational thinking capabilities and apply computational thinking to solve problems that are more constrained and require greater expertise. Supporting Computational Algorithmic Thinking (SCAT) is both a longitudinal between-subjects research project and a free enrichment program supporting and guiding African-American middle school girls over three years as they iteratively design a set of complex games for social change. This article explores Scholars' reflections about the difficulties they faced while using CAT capabilities as they engaged in collaborative game design for social change over those three years. We particularly focus on how these difficulties changed over the course of three years as well as new difficulties that emerged from year to year as Scholars become more expert game designers and computational algorithmic thinkers.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Exploring Collaborative Talk Among African-American Middle-School Girls in the Context of Game Design for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Saunders, Quimeka (Journal of Computing Sciences in Colleges, 2019)
Computer Science education research establishes collaboration among students as a key component in learning, particularly its role in pair programming. Furthermore, research shows that girls, an underrepresented population in computing, benefit from collaborative learning environments, contributing to their persistence in CS. However, too few studies examine the role and benefits of collaborative learning, especially collaborative talk, among African-American girls in the context of complex tasks like designing video games for social change. In this exploratory study, we engage 4 dyads of African-American middle school girls in the task of designing a video game for social change, recording the dyads' conversations with their respective partners over an eight-week summer game design experience during the second year of what has now become a six-year study. Qualitative analysis of dyadic collaborative discussion reveals how collaborative talk evolves over time in African-American middle-school girls.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Digital Conquerors: Minecraft and the Apologetics of Neoliberalism - Dooghan, Daniel (Games and Culture, 2019)
The widespread popularity of sandbox games, and Minecraft in particular, may be a recent phenomenon, but their appeal may be much older. Rather than representing a wholly new development in gaming, these games may participate in a larger media ecology that flatters a neoliberal worldview. This research calls for greater attention to the coercive economic assumptions encoded in gamemechanics. Drawing on scholarship in ludology, postcolonial studies, and phenomenology, it suggests that sandbox games like Minecraft habituate players to myths of empire and capital that rationalize political and economic inequality. More than simply offering a blank slate for player creation, Minecraft rewards players for assuming their entitlement to the world’s resources and thus their superiority over other inhabitants of the game world.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Influence of Black Masculinity Game Exemplars on Social Judgments - Dill, Karen E.; Burgess, Melinda C. (Simulation and Gaming, 2013)
In this investigation, the authors ask how media exemplars of Black masculinity influence the views of and intentions toward other Black men. An experiment compared the effects of exposure to Black video game characters fitting the exemplar thug or street criminal (e.g., Carl Johnson from GRAND THEFT AUTO: SAN ANDREAS) versus exemplars of professional Black men (e.g., political leaders), on evaluations of an unknown and unrelated Black or White political candidate and on pro-Black attitudes. Results revealed significant interactions of exemplar type and candidate race on favorability and capability candidate ratings and on pro-Black attitudes. These data demonstrate the power of mass media exemplars of Black masculinity to prime meaningfully different outcomes in viewers. As the face of gaming evolves with advances in technology, so too should the characterization of race in games.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Mondes profanes: enseignement, fiction et histoire - Éthier, Marc-André 1969-; Lefrançois, David 1976-; Joly-Lavoie, Alexandre; Buysse, Alexandre. (Presses de l'Université Laval, 2018)
"Les bandes dessinées, chansons, films, jeux vidéos, musées, reconstitutions, romans, séries télévisées et voyages occupent de plus en plus de place dans la vie des élèves. Comment exploiter en classe ces biens, loisirs et services culturels d'histoire pour que les élèves posent de mieux en mieux certains actes mentaux que les historiennes et historiens doivent effectuer lorsqu'elles et ils adoptent leur pratique? Pour répondre à cette question, les auteures et auteurs de cet ouvrage explorent les usages scolaires possibles et souhaitables des produits qui ne sont pas associés à l'histoire savante et sur l'exploitation didactique de ce que la Loi québécoise sur les biens culturels désigne comme "?une oeuvre d'art, un bien historique, un monument ou un site historique ... une oeuvre cinématographique, audiovisuelle, photographique, radiophonique ou télévisuelle?". Les auteures et auteurs s'intéressent à des oeuvres qui ne sont pas créées pour l'école, mais qui peuvent néanmoins servir aux enseignantes et enseignants pour faire apprendre l'histoire aux élèves."--Résumé de l'éditeur.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Race and Media: Critical Approaches - Lopez, Lori Kido (New York University Press, 2020)
1. Racism and Mainstream Media / Lori Kido Lopez -- 2. Image Analysis and Televisual Latinos / Mary Beltrán -- 3. Visualizing Mixed Race and Genetics / Meshell Sturgis and Ralina L. Joseph -- 4. Listening to Racial Injustice / Dolores Inés Casillas and Jennifer Lynn Stoever -- 5. Branding Athlete Activism / Jason Kido Lopez -- 6. The Burden of Representation in Asian American Television / Peter X. Feng -- 7. Indigenous Video Games / Jacqueline Land -- 8. Applying Latina/o Critical Communication Theory to Anti-Blackness / Mari Castañeda -- 9. Asian American Independent Media / Jun Okada -- 10. Remediating Trans Visuality / Amy Villarejo -- 11. Intersectional Distribution / Aymar Jean Christian -- 12. Podcasting Blackness / Sarah Florini -- 13. Black Twitter as Semi-Enclave / Raven Maragh-Lloyd -- 14. Arab Americans and Participatory Culture / Sulafa Zidani -- 15. Diaspora and Digital Media / Lia Wolock -- 16. Disrupting News Media / Meredith D. Clark -- 17. Latinx Audiences as Mosaic / Jillian M. Báez -- 18. Media Activism in the Red Power Movement / Miranda J. Brady -- 19. Black Gamers' Resistance / Kishonna L. Gray -- 20. Cosmopolitan Fan Activism / Susan Noh.
Keywords: 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

The Racialized Experiences of Video Games - Venegas, Mario (McNair Scholars Research Journal, 2013)
This research explores the ways different people experience the racial content of video games. Building on DeVane and Squire, this research speaks to content analyses literature that shows games as modern minstrelsies. Using Bonilla-Silva’s definition of Racial Ideology in conjunction with Winddance-Twine’s concept of Racial Literacy, I examined racial ideology and its role as an interpretative framework. I also used Bourdieu's notion of cultural capital to account for video game cultural knowledge. Data were collected through personal interviews where participants played the video game Grand Theft Auto: The Ballad of Gay Tony for 30-50 minutes. A sample of 31 participants covering variation in gender, gaming experience, and race answered questions assessing their racial ideology, then played the game introduction, and finally, answered questions assessing interpretations of game content. Racially aware people with little gaming experience echoed the content analysis minstrelsy findings while colorblind racist non-gamers believed the content accurately represented the world. However, deeper familiarity with gaming and other mass media opened up a new interstitial space for challenging the racial status quo. Racially aware gamers saw the franchises as lampooning the shallow stereotypes in mainstream society. More importantly, with a more sophisticated media context, many colorblind racist gamers also saw racial representations as intentionally offensive. Gamers herein create inventive, non-threatening, but meaningful ways to address racialization across a spectrum of racial literacies. As a result, content analyses need a richer understanding of the experiences of video games for consumers.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Don't Hate the Player, Hate the Game: The Racialization of Labor in World of Warcraft - Nakamura, Lisa (Critical Studies in Media Communication, 2009)
This article examines the racialization of informational labor in machinima about Chinese player workers in the massively multiplayer online role playing game World ofWarcraft. Such fan-produced video content extends the representational space of thegame and produces overtly racist narrative space to attach to a narrative that, whilecarefully avoiding explicit references to racism or racial conflict in our world, is premised upon a racial war in an imaginary world*the World of Azeroth. This profiling activityis part of a larger biometric turn initiated by digital culture’s informationalization of thebody and illustrates the problematics of informationalized capitalism. If late capitalism ischaracterized by the requirement for subjects to be possessive individuals, to make claims to citizenship based on ownership of property, then player workers are unnatural subjects in that they are unable to obtain avatarial self-possession. The painful paradox of this dynamic lies in the ways that it mirrors the dispossession of information workers in the Fourth Worlds engendered by ongoing processes of globalization. As long as Asian ‘‘farmers’’ are figured as unwanted guest workers within the culture of MMOs, user-produced extensions of MMO-space like machinima will most likely continue to depict Asian culture as threatening to the beauty and desirability of shared virtual space in the World of Warcraft.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Replaying Empire: Racialized Violence, Insecure Frontiers, and Displaced Terror in Contemporary Video Games - Leonard, David J.; King, C. Richard (Ethnicity and Race in a Changing World, 2009)
In the wake of 9/11, US popular culture has played an important role in the manufacture of consent and the mediation of contradictions. In particular, video games have aff orded the production of interactive, narrative spaces for the reassertion of race, nation, and gender. Through a close reading of two video games, Gun and Ghost Recon Advanced Warfighter 2, we unpack the insecurities of empire and how racialized violence, colonial categories, and territorial claims work to resecure Whiteness, masculinity, and Americanness. Special attention is given to the militarization of video games and rhetorical struggles over the meaning of race and culture amid the ‘War on Terror’.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Computational Blackness: The Procedural Logics of Race, Game, and Cinema, or How Spike Lee's Livin' Da Dream Productively "Broke" a Popular Video Game - Russworm, TreaAndrea M. (Black Camera, 2018)
How have video games evolved to now create meaningful stories about race and sports? This essay examines how Spike Lee's film-within-a-game, Livin' Da Dream (2015), reproduces some existing procedural and racial logics that reflect the desire to constantly manage and contain the centrality of black athletic greatness in mainstream sports and video game culture. While Lee's long-form cinematic model for turning sports video games into narrative games has been emulated across the medium as a whole, fans and gamers continually discuss the film as an evidently "broken" part of the popular NBA 2K video game series. As I argue here, however, the film-within-a-game productively insists on a default blackness when it functions as what I call "procedural cinema" (a rules and process based narrative). Ultimately, in functioning procedurally, Lee's otherwise conservative melodramatic story serves as a particularly instructive example of how computational blackness may, in systematically subverting the rules of the game, signify disruptively both within and against the machine.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

Kill the Overseer!: the Gamification of Slave Resistance - Lauro, Sarah Juliet. (Forerunners: Ideas First Ser., 2020)
Profiles and problematizes digital games that depict Atlantic slavery and "gamify" slave resistance. In videogames emphasizing plantation labor, the player may choose to commit small acts of resistance like tool-breaking or working slowly. Others dramatically stage the slave's choice to flee enslavement and journey northward, and some depict outright violent revolt against the master and his apparatus. This work questions whether the reduction of a historical enslaved person to a digital commodity in games such as Mission US, Assassin's Creed, and Freedom Cry ought to trouble us as a further commodification of slavery's victims, or whether these interactive experiences offer an empowering commemoration of the history of slave resistance.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

On Video Games: the Visual Politics of Race, Gender and Space - Murray, Soraya (International library of visual culture ; 27, 2018)
Today over half of all American households own a dedicated game console and gaming industry profits trump those of the film industry worldwide. In this book, Soraya Murray moves past the technical discussions of games and offers a fresh and incisive look at their cultural dimensions. She critically explores blockbusters likeThe Last of Us, Metal Gear Solid, Spec Ops: The Line, Tomb Raider and Assassin's Creed to show how they are deeply entangled with American ideological positions and contemporary political, cultural and economic conflicts.As quintessential forms of visual material in the twenty-first century, mainstream games both mirror and spur larger societal fears, hopes and dreams, and even address complex struggles for recognition. This book examines both their elaborately constructed characters and densely layered worlds, whose social and environmental landscapes reflect ideas about gender, race, globalisation and urban life. In this emerging field of study, Murray provides novel theoretical approaches to discussing games and playable media as culture. Demonstrating that games are at the frontline of power relations, she reimagines how we see them - and more importantly how we understand them.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Have Always Been Queer. - Ruberg, Bonnie (New York University Press, 2019)
While popular discussions about queerness in video games often focus on big-name, mainstream games that feature LGBTQ characters, like 'Mass Effect' or 'Dragon Age', Bonnie Ruberg pushes the concept of queerness in games beyond a matter of representation, exploring how video games can be played, interpreted, and designed queerly, whether or not they include overtly LGBTQ content. 'Video Games Have Always Been Queer' argues that the medium of video games itself can-and should-be read queerly. In the first book dedicated to bridging game studies and queer theory, Ruberg resists the common, reductive narrative that games are only now becoming more diverse. Revealing what reading D.A. Miller can bring to the popular 2007 video game 'Portal', or what Eve Sedgwick offers 'Pong', Ruberg models the ways game worlds offer players the opportunity to explore queer experience, affect, and desire. As players attempt to 'pass' in 'Octodad' or explore the pleasure of failure in 'Burnout: Revenge', Ruberg asserts that, even within a dominant gaming culture that has proved to be openly hostile to those perceived as different, queer people have always belonged in video games-because video games have, in fact, always been queer.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Virtual History: How Videogames Portray the Past - Wainwright, A. Martin (Routledge, 2019)
Virtual History examines many of the most popular historical video games released over the last decade and explores their portrayal of history. The book looks at the motives and perspectives of game designers and marketers, as well as the societal expectations addressed, through contingency and determinism, economics, the environment, culture, ethnicity, gender, and violence. Approaching videogames as a compelling art form that can simultaneously inform and mislead, the book considers the historical accuracy of videogames, while also exploring how they depict the underlying processes of history and highlighting their strengths as tools for understanding history. The first survey of the historical content and approach of popular videogames designed with students in mind, it argues that games can depict history and engage players with it in a useful way, encouraging the reader to consider the games they play from a different perspective. Supported by examples and screenshots that contextualize the discussion, Virtual History is a useful resource for students of media and world history as well as those focusing on the portrayal of history through the medium of videogames.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Digital Saint-Domingue: Playing Haiti in Videogames - Lauro, Sarah Juliet (Archipelagos, 2017)
This article comes out of a longer project looking at digital commemorations of slave rebellion. In this excerpt from that work, the author considers the issues at stake in videogamic representations of colonial Saint Domingue and its denizens, particularly for their depiction of the prehistory of the Haitian Revolution. In two mainstream videogames, both part of the Assassin’s Creed franchise, the history of Saint Domingue, its legacy of slave resistance, and the Haitian Revolution are made into fodder for an interactive entertainment experience that intervenes in and reshapes history in a complex manner. There are several issues at stake, which the author focuses on exclusively in terms of the commodification of Saint Domingue. First, the games place the history of slave revolt into the hands of game players of diverse ancestry, allowing for a redistribution of ownership over narratives of emancipation and empowerment. Second, the games identify themselves as tampering with history, and their mélange of fictional characters and real personages seems to risk rewriting the history of Saint Domingue’s legacy of slave revolt and—by extension—of the Haitian Revolution itself. Given recent events in the United States, and increased attention to strategies of black resistance such as the Black Lives Matter movement, it seems all the more imperative that our depiction of slave revolts in popular culture be handled with care. And yet, the author finds a subversive maneuver visible in the games: the use of untranslated language, especially Haitian Kreyol, may work to preserve and limit the player’s mastery over these histories. This article provides a tour of this complex territory of digital Saint Domingue.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Avatars of Whiteness: Racial Expression in Video Game Characters - Dietrich, David R. (Sociological Inquiry, 2013)
Video games are an enormous segment of popular media today, comparable to tele-vision and movies. Moreover, video games represent a new form of media distinguishedfrom previous forms due to the interactive element, where game players have the ability to change and influence the game world. This paper contributes to the study of race and popular media by examining how race is presented in role-playing video games throughthe feature of avatar creation. Capabilities for avatar creation are analyzed in over sixty massively multiplayer online role-playing games (MMORPGs) in service as of early2010 and twenty offline role-playing games (RPGs) published over the past 10 years.The analysis shows that the vast majority of games, both online and offline, do not allow for the creation of avatars with a non-white racial appearance. Forcing an Angloappearance on avatars that purport to represent the player has the potential to reinforce asense of normative whiteness as well as shape the social composition of online worldsinto all-white virtual spaces, contributing to the creation of a virtual“white habitus.”
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Pedestal, A Table, A Love Letter: Archaeologies of Gender in Videogame History - Nooney, Laine (Game Studies, 2013)
The history of videogames has largely been imagined as a patrilineal timeline. Women, when they emerge as participants in the game industry, are typically figured as outliers, exceptions, or early exemplars of “diversity” in the game industry. Yet the common practice of “adding women on” to game history in a gesture of inclusiveness fails to critically inquire into the ways gender is an infrastructure that profoundly affects who has access to what kinds of historical possibilities at a specific moment in time and space. This contribution aims to shift the relevant question from “Where are women in game history?” to “Why are they there in the way that they are?” To do so, the essay strategically deploys Sierra On-Line co-founder and lead designer Roberta Williams as an exceptional case study on the problem of gender in videogame history. Drawing from both media archaeology and feminist cultural studies, this contribution first outlines the function Roberta Williams serves as a gendered subject of game history. The remainder of the essay is organized as three short, non-chronological vignettes about specific objects and practices in the biography of Roberta Williams. Attention to the contextual specificity of Roberta Williams and her historical moment produces an alternative genealogy for gaming centered around relations of intimacy and labor in domestic space. Rather than producing a chronology, the method of this essay illustrates a historical critique by sketching a contour that unsettles the presumptive logic of what we must account for when we write about the objects and subjects of game history.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Race-based fantasy realm: Essentialism in the world of warcraft - Monson, Melissa J. (Games and Culture, 2012)
This article explores issues of racial essentialism and ethnicity in the massively multiplayer online role-playing game World of Warcraft (WoW). The fantasy world of Azeroth mirrors elements of real-world race-based societies where culture is thought to be immutably linked to race. The notion of biological essentialism is reinforced throughout the gamescape. Race plays a primary role in the social and political organization of Azeroth. Among other things, race determines alliances, language, intellect, temperament, occupation, strength, and technological aptitude. The cultural representation of the respective racial groups in WoW draws upon stereotypical imagery from real-world ethnic groups (e.g., American Indian, Irish/Scottish, Asian, African, etc.).
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

What's in a Game? Race, Gender, and LGB Representation in Video Games - Wilberg, Heather (Roosevelt University, 2011)
Though research examining violence in video games (VGs) and its potential real-world effects has been a target of academic attention, content analysis of demographical marginalization in VGs has not been as prolific. What little research there is reveals a pronounced absence and stereotyping of women and racial or ethnic minorities but ignores queer content altogether. This work explores video game demographics through quantitative analysis of the demographic composition and stereotyping of characters from 30 popular VG titles. Findings of this study support that of past analyses, evidencing that the representation of women and racial minorities is both rare and stereotyped. Queer characters are also shown to be sparse and stereotyped. While past research has largely treated race and gender separately, this study shows that multiply marginalized groups, including queers, are even more underrepresented and stereotyped. The sociocultural implications of these findings are discussed and suggestions are made for future analysis and marketing.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Blackless Fantasy: The Disappearance of Race in Massively Multiplayer Online Role-Playing Games - Higgin, Tanner (Games and Culture, 2009)
This article focuses on questioning and theorizing the visual and discursive disappearance of blackness from virtual fantasy worlds. Using EverQuest, EverQuest II, and World of Warcraft as illustrative of a timeline of character creation design trends, this article argues that the disappearance of blackness is a gradual erasure facilitated by multicultural design strategies and regressive racial logics. Contemporary fantasy massively multiplayer online role-playing games (MMORPGs) privilege whiteness and contextualize it as the default selection, rendering any alterations in coloration or racial selection exotic stylistic deviations. Given the Eurocentrism inherent in the fantasy genre and embraced by MMORPGs, in conjunction with commonsense conceptions of Blacks as hyper-masculine and ghettoized in the gamer imaginary, players and designers do not see blackness as appropriate for the discourse of heroic fantasy. As a result, reductive racial stereotypes and representations proliferate while productive and politically disruptive racial differences are ejected or neutralized through fantastical proxies.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The U.S. Video Game Industry: Analyzing Representation of Gender and Race - Dunlop, Janet C. (International Journal of Technology and Human Interaction, 2007)
Today’s media are vast in both form and influence; however, few cultural studies scholars ad-dress the video gaming industry’s role in domestic maintenance and global imposition of U.S. hegemonic ideologies. In this study, video games are analyzed by cover art, content, and origin of production. Whether it is earning more “powers” in games such as Star Wars, or earning points to purchase more powerful artillery in Grand Theft Auto, capitalist ideology is reinforced in a subtle, entertaining fashion. This study shows that oppressive hegemonic representations of gender and race are not only present, but permeate the majority of top-selling video games. Finally, the study traces the origins of best-selling games, to reveal a virtual U.S. monopoly in the content of this formative medium.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

The potential of America's Army, the Video Game as Civilian-Military Public Sphere - Li, Zhan (Massachusetts Institute of Technology, 2003)
The US Army developed multiplayer online First Person Shooter video game, America's Army, was examined as the first instance of an entirely state-produced and directed enterprise leveraging video game popular culture. Specifically, this study is concerned with the potential of the America's Army gamespace as a US civilian-military public sphere of the Information Age, as assessed through Habermasian theories of democratic communication. Interview fieldwork was carried out in several America's Army game communities including those of real-life military personnel, Christian Evangelicals, and hackers. The political activities of these exceptional game communities are considered for the ways they escape and transcend current critical theories of Internet-based public spheres.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé